Realist criminology - Matthews, Roger (Palgrave Macmillan, 2014)
"Criminology has expanded significantly as an academic discipline, but it has been argued that it is becoming increasingly socially and politically irrelevant. This books aims to address this problem by rethinking the theoretical underpinnings and research methods we use, to form a criminology that is critical, engaged and useful. The left realist approach to criminology has changed considerably over the past twenty years and continues to make an important contribution to the theoretical study of crime, as well as issues such as crime prevention, policing, prisons, and community safety. As one of the pioneers of realist criminology, Roger Matthews presents a coherent overview of its development and continued relevance. By providing a critique of some of the dominant approaches in criminology, this book sets a new agenda for theoretical and practical engagement and will appeal to all those interested in making sense of contemporary forms of social control and developing types of analysis and intervention which are designed to produce a more effective and just criminal justice system. "--